Young Spouses' Experiences of Having a Partner With Heart Disease and Adolescents Living at Home - Matilda Holmbom; Frida Andréasson; Hanna Grundström; Camilla Bernild; Nina Fålun; Tone Merete Norekvål; Selina Kikkenborg Berg; Anna Strömberg (Wiley, 2024)
ABSTRACT Aim To describe the life situation of spouses having a partner with heart disease and adolescents living at home. Design Qualitative inductive design. Method Participants (n = 22) were included from three Scandinavian countries. Semi‐structured interviews were analysed using thematic analysis with an inductive and latent approach. Results Three themes were derived. 'Being in spousal and parental role transition' described how daily life had been affected and parental responsibilities had been doubled due to their partner's heart disease. 'Living with unpredictability and insecurity' included how the unpredictable illness trajectory caused worries and affected the well‐being of the family. 'Managing a challenging life situation' highlights how spouses coped with their partners' heart disease and adapted to a new life situation. Conclusion Young spouses' life situation was greatly affected by their partner's heart disease, resulting in increased responsibilities and double parenthood. Having a positive attitude and mindset towards life was used as a strategy to cope with the changed life situation and find a new way of life. Implications for the Profession and/or Patient Care All family members are affected by heart disease. Spouses needed additional professional support and guidance on how to involve the children when a parent is ill. Impacts This study highlights how young spouses, with adolescents living at home, experience their life situation. The life situation is unpredictable due to the partner's heart disease, as they must handle both caring for their partner and taking on double parenthood. Research involving family members can improve person‐ and family‐centred care and treatment outcomes in health care and society. Reporting Method COREQ checklist was used preparing the manuscript. Patient or Public Contribution Data collection included interviews with spouse. What Does This Paper Contribute to the Wider Global Clinical Community? By highlighting the spouses changed life situation due to heart disease and the importance of including them in health care.